Pengaruh Stress Kerja terhadap Ketidakpuasan Kerja dengan Counterproductive Work Behavior (CWB) sebagai Variabel Mediasi dalam Perspektif Bisnis Islam: (Studi pada Karyawan Mie Gacoan Cabang Wayhalim) - Indy Satya Ayu Esa Ningrum; Any Eliza; Okta Supriyaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the current era of globalization, human resources in a company play a very important role. The concentration of human resources is centered on people who have work ties in the company so that they can improve employee performance in it. One of the things that most affects employee performance is job dissatisfaction. Researchers added counterproduction work behavior as a mediating variable to consider employee reasons, why employees feel work stress towards job dissatisfaction. This study aims to determine the effect of work stress on job dissatisfaction with counterproduction work behavior as a mediating variable. This type of research is quantitative with an associative nature. The population in this study were employees of the Wayhalim branch of Mie Gacoan with a sample of 53 respondents, because this study used a non-probability sampling technique which was a saturated sampling type. Data processing with SmartPLS. Based on the research that has been done, the results are in accordance with the research hypothesis, namely that there is a positive and significant influence between work stress and job dissatisfaction. Work Stress has a positive and insignificant effect on counterproduction work behavior. Counterproduction work behavior has a positive and insignificant effect on job dissatisfaction. Counterproduction work behavior has a positive and insignificant effect on Job Stress and job dissatisfaction.